Pengaruh Komitmen Kerja Dan Pemberdayaan Pegawai Terhadap Pelayanan SP2HP Dan Sidik Jari Pada Sat. Reskrim Banjar - Aef Kusyanto; Apri Budianto; Ferey Herman (CV. Aksara Global Akademia, 2023)
The background of this research was to determine work commitment and employee empowerment towards SP2HP and Fingerprint services on Sat. Banjar Criminal. This study uses a quantitative descriptive method, with the result that work commitment has a significant effect on SP2HP services and fingerprints. This means that if work commitment is increased, SP2HP and fingerprint services will also increase. Employee empowerment has a significant effect on SP2HP and fingerprint services. This means that if employee empowerment is increased, SP2HP and fingerprint services will also increase. Work commitment and employee empowerment have a significant effect on SP2HP and fingerprint services. This means that if work commitment and employee empowerment are increased, SP2HP and fingerprint services will also increase